2001
DOI: 10.1080/15287390152410165
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Styrene Metabolite 4-Vinylphenol by Rat and Mouse Liver and Lung

Abstract: Styrene is a widely used chemical in the reinforced plastics industry and in polystyrene production. Its primary metabolic pathway to styrene oxide and then to styrene glycol, which is further metabolized to mandelic acid and phenylglyoxylic acid, has been well studied. However, a few studies have reported finding a minor metabolite, 4-vinylphenol (4-VP), in rat and human urine. The present studies sought to determine if the formation and metabolism of 4-VP in rat and mouse liver and lung preparations could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…4-VP is an intermediate (and hence indicator) of the ring-oxidation pathway and was identiWed as a minor metabolite in the urine of rats (Pantarotto et al, 1978) and exposed workers (PfäZi et al, 1981). In in vitro experiments 4-VP formation by lung and liver microsomes of mice and rats was not conWrmed (Carlson et al, 2001). Considerable 4-VP metabolizing activity, as detected by the loss of 4-VP, was observed by these authors in the preparations, the activity being much higher in mouse than in rat tissues, suggesting that 4-VP may be a short-lived intermediate.…”
Section: Introductionmentioning
confidence: 75%
“…4-VP is an intermediate (and hence indicator) of the ring-oxidation pathway and was identiWed as a minor metabolite in the urine of rats (Pantarotto et al, 1978) and exposed workers (PfäZi et al, 1981). In in vitro experiments 4-VP formation by lung and liver microsomes of mice and rats was not conWrmed (Carlson et al, 2001). Considerable 4-VP metabolizing activity, as detected by the loss of 4-VP, was observed by these authors in the preparations, the activity being much higher in mouse than in rat tissues, suggesting that 4-VP may be a short-lived intermediate.…”
Section: Introductionmentioning
confidence: 75%
“…They suggested that the 4-VP was formed via the 3,4-oxide and was further metabolized to 4-hydroxystyrene-7,8-glycol . In recent studies we were unable to demonstrate the formation of 4-VP from styrene in rodent microsomal preparations but found that 4-VP was rapidly metabolized by mouse and rat hepatic and pulmonary microsomes involving CYP2E1 and CYP2F2 (7). In a recent study in which rats and mice were exposed by inhalation to [ring-U- 14 C]styrene, Boogaard et al (5) reported nding 14 CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Microsomal preparations of mouse liver and lung appeared to be EFSA Journal 2011; 9(5):1990 far more active than microsomes from the same tissues in the rat. In addition, metabolism of 4-vinylphenol in mouse lung microsomes was also observed to occur with glutathione, also in absence of an active cytochrome P450 system (Carlson et al, 2001;Carlson et al, 2002). However, 4-vinylphenol is not a potent GSH-depleting agent in liver and lung tissue in vivo (Turner et al, 2005).…”
Section: Vinyl-and Alkoxy-substituted Phenolmentioning
confidence: 98%